Digestion versus abrasion features in rodent bones. (7th April 2014) - Fernández‐Jalvo, Yolanda; Andrews, Peter; Sevilla, Paloma; Requejo, Virginia
<x xml:space="preserve">Abstract</x> The origin of most fossil small mammal assemblages is predation by avian or mammalian predators. Bone corrosion by gastric juices observed in these fossils is direct evidence of digestion, and traits of digestion indicate the type of predator involved. However, certain features observed in digested bones, such as rounding and polishing, are similar to the rounding and polishing produced by other processes, particularly abrasion, in which predation is not involved. Misidentification of digestion has major repercussions in palaeoenvironmental and palaeoclimatic interpretations as well as interpretations of biostratigraphy and potential reworking. Digestion is directional and progressive process, primarily affecting the most mineralized tissues (enamel) advancing from the tips to the centre of the anatomical element. In contrast, abrasion identically affects any type of osseous tissue homogeneously rounding the entire skeletal element. Microscopically, digested bones display a distinctive chemical corrosion ('tornlike' appearance), whilst abraded bones appear smooth with microstriations and pitting microwear. Here, we present the results of a series of experiments designed to establish new and clear criteria to distinguish bone rounding and polishing caused by digestion from that originating from abrasion.